MULTIVESSEL DISEASE AS A PROGNOSTIC MARKER IN PATIENTS PRESENTING FOR PRIMARY PERCUTANEOUS CORONARY INTERVENTION - Batra, Mahesh Kumar; Rasool, Syed Ishtiaq; Solangi, Bashir Ahmed; Khan, Naveedullah; Karim, Musa; Rizvi, Syed Nadeem Hassan (Journal of Ayub Medical College Abbottabad, 2018)
Background: Multi-vessel disease is associated with higher mortality rates in ST-Elevation Myocardial Infarction (STEMI) patients, which may further alter clinical course and decision making. Hence, the purpose of this study is to determine prevalence, in hospital and early after discharge (up to 30 days) outcome of patients with multi-vessel disease as compared to single vessel disease presenting with acute STEMI undergoing Primary PCI. Methods: This study includes 282 consecutive selected patients, presented in emergency department with acute STEMI; undergo primary percutaneous coronary intervention (PCI) at Catheterization Laboratory of National Institute of Cardiovascular Diseases (NICVD), Karachi Pakistan during the study period of 17th December 2016 to 16th June 2017. Demographic characteristics, clinical history, post procedural complications, and short term adverse clinical events in patients with SVD and MVD were assessed and compared using z-test, t-test, and Fisher’s Exact test. Results: Comparing the patients with single vessel disease, multi-vessel disease patients have worse post procedural outcomes, increased overall complications, length of hospital stay, higher referral for CABG, and in-hospital mortality. On follow up relatively higher, but not statistically significant, patient with MVD developed recurrence of symptoms and got re-admission. Conclusion: Multi-vessel disease in patients presenting for primary PCI is the direct indicative of significantly higher post procedure complications, mortality, morbidity, and prolonged hospitalization. Also, risk of recurrence of symptoms and re-admission remains high in patients with multi-vessel disease. Keywords: Multi-vessel disease; Primary percutaneous coronary intervention, PCI; ST-Elevation Myocardial Infarction, STEMI